Atherosclerosis, Arteriosclerosis and Arteriolosclerosis - Gianturco, Luigi (IntechOpen, 2020)
With high morbidity and mortality rates, atherosclerosis (ATS) is a major concern worldwide. This book provides comprehensive information on ATS, including chapters on cardiovascular disease and obstructive sleep apnea, rheumatology and cardiovascular risk, and the differences of ATS among men and women. Let's hope for the best and thank you to all my team for collaborating in this book production. In particular, thanks • to Bruno (my expert colleague) and Aurel (my secretary) for analyzing and reading with me all the texts • to Vincenzo, Stefano and Andrea for English evaluation • and finally to Rebecca (my future wife) for sustaining me in all professional activities giving me power in daily life!